Strategi Penerapan Green Computing Pada Unit Pengelola Sistem Informasi Pembelajaran Berdasarkan Metode Pendekatan Analytic Network Process(ANP): Studi Kasus SMPN 109 Jakarta - Hariyanto Hariyanto (STMIK Budi Darma, 2019)
Information technology is evolving so fast in the era of globalization influence in making a very important decision to be taken in dealing with existing problems. Decision-making can be influenced by several aspects, it greatly affects the speed in making decisions by the decision maker, where decisions must be taken quickly and accurately. This study was made by using the Analytical Network Process (ANP). Where the algorithm is doing the counting process to find the best decision, ie by calculating the value criteria and comparing it to the calculation of the probability of each decision to be taken. This research will be used to assist the decision maker in determining the application of the strategy alternatives Green Computing. The criteria used in the implementation of the Green Computing strategies according to the needs that exist in the SMP 109 Jakarta. From the research, Green Computing Implementation Strategies In Unit Information System Manager Learning Approach Method Based Analytic Network Process (ANP). Decision Support System will generate the right decision and flexible with the aspects that influence the decision, and to produce a report to the decision maker in order to assist the decision maker in making decisions.